PENGARUH PENDAPATAN NEGARA, BELANJA NEGARA, DAN INVESTASI PMDN TERHADAP PENERIMAAN PAJAK DI INDONESIA TAHUN 2020–2024 DALAM PERSPEKTIF KEBIJAKAN FISKAL KONTEMPORER - Imaniar Septiani Rais; Qimyatussa'adah; Hedi Pandowo (Universitas Merdeka Madiun, 2025)
This study aims to examine the impact of state revenue, government spending, and domestic investment (PMDN) on taxrevenues in Indonesia from 2020 to 2024 in the perspective of contemporary fiscal policy. Using multiple linear regression with SPSS22, the study finds that each variable has a significant influence both partial and simultaneous on tax revenue (significance value =0.000). The fiscal index contributes to increasing tax revenue by enhancing purchasing power and economic growth, while PMDNinvestment promotes job creation and tax base expansion. With a determination coefficient (R²) of 0.720, the model shows that 72% ofthe tax revenue variation is explained by these three variables. The study supports Keynesian and Laffer Curve theories andrecommends optimizing fiscal policy to enhance sustainable tax revenue.